Unicornuate uterus: case reports of heterogenous presentations challenging clinical diagnosis and management - Trivedi, Swati; Khokher, Santosh; Rastogi, Prasoon; Dhaka, Vinod Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Unicornuate uterus is an anomaly arising from defective lateral fusion of incompletely developed mullerian duct or paramesonephric duct with the contralateral duct. Pregnancy in non-communicating rudimentary horn can result in I and II trimester pregnancy losses along with maternal morbidity and mortality. Here we describe three such cases of unicornuate uterus with non-communicating rudimentary horn pregnancy, who presented to our hospital with pain in lower abdomen. Two of them with II trimester pregnancy landed in haemorrhagic shock owing to rupture of pregnant horn, though were revived by immediate intervention. Third patient who came with a definitive diagnosis of I trimester rudimentary horn pregnancy was managed electively by hemi-hysterectomy. Rupture of pregnant uterus can occur in II trimester when associated with uterine anomaly. Early sonographic diagnosis has a major offering in workup, management and prevention of mother from grave life threatening consequences.